Pengaruh Current Ratio, Return On Asset, Total Asset Turn Over Terhadap Nilai Perusahaan Di Perusahaan Manufaktur - Rizki; Desi; Yuli Nurhayati; Gita Juliani; Yulia Angrainy; Niswatul Akhyari (CV. ITTC INDONESIA, 2025)
This research is a literature study. which will discuss previous theories and research on the Influence of Current Ratio, Return On Asset, Total Asset Turnover on company value in manufacturing companies. The method used is quantitative descriptive analysis where the data used is in the form of theory and calculation of current ratio, return on assets, total asset turnover, and company value. The results of the study indicate that research that has been conducted by previous researchers, overall the current ratio affects company value. research that has been conducted by previous researchers, overall That the Influence of return on assets has an influence on company value Research that has been conducted by previous researchers, overall That total asset turnover affects company value, Overall the results of 30 previous studies can be stated that the variables current ratio, return on Asset, Total Asset Turnover have an influence on each other on company value